1988
DOI: 10.1111/j.1749-6632.1988.tb38554.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Novel Series of Selective Inhibitors of Arachidonate 5‐Lipoxygenase on Anaphylactic and Inflammatory Responses

Abstract: In conclusion, we have described a novel series of acetohydroxamic acids that are potent and selective inhibitors of arachidonate 5-lipoxygenase in vitro and in vivo. In addition, we have shown that these compounds attenuate "leukotriene-dependent" anaphylactic bronchospasm, the accumulation of inflammatory leukocytes, and the development of fever in experimental models. It now remains to be determined if these compounds have any therapeutic value in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…Since these compounds are rela tively selective inhibitors of 5-lipoxygenase and capable of inhibiting LTB4 production (14), one of the chemo tactic factors involved in the model is likely to be LTB4. It has been reported that 5-lipoxygenase inhibitors of the redox type, such as NDGA, were inactive when ad ministered orally (19). However, in our evaluation by oral treatment with AA-861, BW-755C (20) and the 4-acyl aminophenol derivatives, all of which are of the redox type, the latter two, but not AA-861, were effective (Figs.…”
Section: Discussioncontrasting
confidence: 44%
“…Since these compounds are rela tively selective inhibitors of 5-lipoxygenase and capable of inhibiting LTB4 production (14), one of the chemo tactic factors involved in the model is likely to be LTB4. It has been reported that 5-lipoxygenase inhibitors of the redox type, such as NDGA, were inactive when ad ministered orally (19). However, in our evaluation by oral treatment with AA-861, BW-755C (20) and the 4-acyl aminophenol derivatives, all of which are of the redox type, the latter two, but not AA-861, were effective (Figs.…”
Section: Discussioncontrasting
confidence: 44%
“…However, the reduced mucosal synthesis of LTC4 may occur in part as a consequence of a reduction in ethanol-induced damage. Although NDGA is a potent inhibitor of lipoxygenase enzymes in vitro (Hamberg, 1986;Bhattacherjee et al, 1988) we have been unable to demonstrate inhibition of lipoxygenase by NDGA in rat whole blood ex vivo . A further possibility is that BW 755C may act by inhibiting 12-or 15-lipoxygenase (Randall et al, 1980) and that products from these enzyme pathways, such as hydroperoxy metabolites, are involved in ethanol-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…3e). With this in mind specific cyclo-oxygenase and lipoxygenase inhibitors, (ibuprofen and BWA 137c respectively [3]) were tested for activity in the in vitro virus growth assay; neither of these compounds enhanced HSV-1 growth, or CPE, in L929 cells (data not shown). 3g).…”
Section: Bha Reverses Virus-induced Cpe and Enhances Hsv-1 9rowth In mentioning
confidence: 99%